(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
The Aim Of This Study Is To Reveal The Journalistic Status Of Reda Houhou Through His Articles In Al-Basa’ir And Al-Shu’ala, Highlighting The Main Issues He Focused On And The Objective Of His Writings, Which Was To Critique French Policies And Later Guide Algerian Politics. As One Of The Prominent Contemporary Algerian Intellectuals, Reda Houhou Played A Significant Role In Resisting French Colonialism. Through His Writings In Al-Basa’ir And Al-Shu’ala During The Years 1950 And 1951, He Fought Against All Forms Of Submission To The Occupation. In Doing So, He Created A Landmark Of Cultural Resistance In Every Place He Visited. Using The Historical And Analytical Method, We Aim To Deduce The Various Issues Discussed By Reda Houhou, Emphasizing His Stance On Colonial Policies, Which Earned Him A Prestigious Position In Algeria And Abroad Before And After Algeria’s Independence. Keywords: Ahmed Reda Houhou, Al-Shu’ala Newspaper, His Journalistic Status.